Conflict, Crime, and the State in Postcommunist Eurasia - Arsovska, Jana; Jonsson, Michael; Cornell, Svante E. (Book collections on Project MUSE., 2014)
Conflict, Crime, and the State in Postcommunist Eurasia examines the emergence and evolution of a crime-conflict nexus and the relationship between ideologically motivated insurgents and profit-motivated criminal organizations in the region.